Information and communication technology and their impact in the marketing of tourist services Field study in the eye of tourist or /تكنولوجيا المعلومات والاتصالات واثرها في تسويق الخدمة السياحية دراسة ميدانية في عينة من المنظمات السياحية في محافظة بغداد (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
We seek through the current study, research and analysis research and analysis of information technology and basic component, appliances, hardware, software, applications and communications, human resources, and measure their impact on the marketing of tourist service through the dimensions of reliability, responsiveness and courtesy, which is owned in the number of tourist organizations in Baghdad, through the adoption  a questionnaire form prepared for this purpose. Given the vital role of information and communication technologies to facilitate the functions of the different organizations, this because this technology owns the capabilities and optional at the basic and sub level components  achieving interaction and communication  between the different organizations and their customers and clients.At the same time tourist services  have become in desperate need of the means of scientific and advanced techniques both to view these services or marketed, developed or provided according to the characteristics and requirements and standards, Especially since the tourist service requires identifying means to customers as well as providing services to clients and customers and required the  techniques that makes them available at all times. The study reached many conclusions, which was established under which fitted the recommendations of the surveyed tourism organizations, and similar tourism organizations across the country.